Effect of risk control as moderator of relationship between government support, training, digital marketing, financial capital and performance of SMEs in Indonesia - Puspa Liza, Ghazali; Juliana, Arifin; Salman, Lambak; Dede Ansyari, Guci; Abdul Talib, Bon (2021)
This research focus on effect of risk control as moderator of relationship between government support, training, digital marketing, financial capital and performance of SMEs in Indonesia. The purpose of the research is to determine the effect of risk control on performance of SMEs in Indonesia. The respondent in this research were all SMEs players in Medan, North Sumatera Province, Indonesia. The data self-collected, using quantitative based-study. Data will be collect by surveyed questionnaire and be analyzed by using Structural Equation Model (SEM) Amos. Three hundred respondents of people who become SMEs players in Medan, Indonesia. The methode instrument was using questionnaires and made up of seven variables, where four were exogenous variables, one was moderating and one was endogenous variable. By using confirmatory factor analysis (CFA), it is found that each variable has strong correlation. it can be concluded that risk control has positive significant effect as moderator between government support, training, digital marketing, financial capital and performance of SMEs.